A phase II randomized clinical trial of the effect of metformin versus placebo on progression-free survival in women with metastatic breast cancer receiving standard chemotherapy. (December 2019) - Pimentel, Isabel; Lohmann, Ana Elisa; Ennis, Marguerite; Dowling, Ryan J.O.; Cescon, David; Elser, C.; Potvin, K.R.; Haq, R.; Hamm, C.; Chang, Martin C.; Stambolic, Vuk; Goodwin, Pamela J.
Abstract: Objectives: Pre-clinical data suggest metformin might enhance the effect of chemotherapy in breast cancer (BC). We conducted a Phase II randomized trial of chemotherapy plus metformin versus placebo in metastatic breast cancer (MBC). Material and methods: In this double blind phase II trial we randomly assigned non-diabetic MBC patients on 1st to 4th line chemotherapy to receive metformin 850 mg po bid or placebo bid. Primary outcome was progression-free survival (PFS); secondary outcomes included overall survival (OS), response rate (RR), toxicity and quality of life (QOL). With 40 subjects and a type-one error of 0.2 (one-sided), a PFS hazard ratio (HR) of 0.58 could be detected with 80% power. Results: 40 patients were randomized (22 metformin, 18 placebo) with a mean age of 55 vs 57 years and ER/PR positive BC in 86.4% vs 83.3% off metformin vs placebo, respectively. Mean BMI was 27kg/m2 in both arms. The majority of patients were on 1st line chemotherapy. Grade 3–4 toxicity occurred in 31.8% (metformin) vs 58.8% (placebo). Best response: Partial response 18.2% metformin vs 25% placebo, stable disease 36.4% metformin vs 18.8% placebo, progressive disease 45.4% metformin vs 56.2% placebo. Mean PFS was 5.4 vs 6.3 months (metformin vs placebo), HR 1.2 (95% CI 0.63–2.31). Mean OS was 20.2 (metformin) vs 24.2 months (placebo), HR 1.68 (95% CI 0.79–3.55). Conclusion: In this population metformin showed no significant effect on RR, PFS or OS. These results do not support the use of metformin with chemotherapy in non-diabetic MBC patients. Highlights: The addition of metformin to standard chemotherapy in non-diabetic metastatic breast cancer patients showed no significant effect on response rate, PFS or OS, as compared to placebo. Metformin was associated with increased grade I and II adverse events and decreased global quality of life.